Кераміка середньовічного Білгорода: візантійський посуд із розкопок Л. Д. Дмитрова та А. І. Фурманської - Тесленко, І.Б.; Мироненко, Л.В. (Археологія, 2023)
У статті репрезентовано колекцію довізної візантійської кераміки з розкопок середньовічного Білгорода 1947, 1949, 1950 і 1953 рр., що зберігається в Інституті археології НАН України. Окрему увагу
приділено аналізу стратиграфічної ситуації на ділянці розкопу та питанням хронології досліджених
тут культурних шарів і будівельних горизонтів, із
яких походить керамічний матеріал. У складі візантійського посуду виділено п’ять технологічних
груп, що надходили до міста впродовж кінця XIII —
першої половини XV cт. Деталізовано хронологічну
позицію кожної з них, запропоновано версії щодо
їхнього походження та окреслено ареал поширення
в Причорноморському й Середземноморському регіонах. The focus of the study is Byzantine pottery together with its archaeological context from the excavations of Bilhorod (Bilhorod-
Dnistrovskyi, Odesa Oblast, Ukraine), led by L. D. Dmitrov in 1945, 1947, 1949, 1950, and A. I. Furmanska in 1953, which is
kept in the Scientific Repository of the Institute of Archaeology of the NAS of Ukraine. First of all, the authors concentrated on the
analysis of the stratigraphic data at the excavation site and the chronology of its cultural layers and building horizons, from which
the ceramic material originates. An analysis of the numismatic finds showed the existence of residential buildings in the studied area
from the end of the 13th century until about the middle of the 15th century. The latest date is particularly interesting, because it was
previously thought that the quarter ceased to exist at the beginning of the 15th century.
Then, based on the visually detectable features of the raw materials, there were identified five technological groups of
earthenware pottery in the Byzantine imported ceramics from these excavations and their chronological position, area of distribution,
and possible localisation of their workshops were specified.
The first of them is similar to the Novy Svet (NS) group (fig. 3). It belongs to the heterogenous SCC (Sgraffito with Concentric
Circles) stylistic family. The peak of the spread of such pottery in the Northern Black Sea region was between the last third of the
13th — the beginning of the 14th century. Such ceramics were produced in many workshops of the Black Sea and the Mediterranean,
but the origin of the NS group has not been clarified yet.
The second group of tableware morphologically and stylistically quite varied (fig. 4; 5: 5—9; 6: 1—8, 11; 7; 8: 1—3). It
probably originated from the pottery centres that functioned for a long time, at least from the late 13th to the mid-15th century. Some
of decorative series (SCC, with 8-shaped figures, monograms, with thin strips of dark green painting and others) can be used as
chronological indicators for different periods of time between late 13th to the mid-15th centuries. The results of archaeometrical
study are introduced at least for some of the stylistic series that allowed associating its origin, with the ceramic workshops of
Constantinople the remains of which were found in the Sirkeci neighborhood in the Eminönü quarter of the Fatih district in Istanbul,
Turkey. All the mentioned above was the most interesting, because it provided data for clarifying both the chronology of the activity
of these workshops and the different types of its wares in future perspectives.
The ceramics of the third (the EIW stylistic family), and the fifth (kitchen glazed ware) groups (fig. 5: 1—4 and 8: 5) had also a
precise chronology and so could be used as indicators for dating the archaeological contexts within the second half of the 14th — the
beginning of the 15th century and the end of the 13th — the second third of the 14th century respectively. The origin of both groups
is yet to be explicated.